2008-as világgazdasági válság kialakulásának okai - Kurtucz Csaba (Geopolitikai szemle, 2020)
The 2008 Great Recession started from the subprime mortgage crisis in the United States. The dynamic growth in the value of real estate and overly liberal lending made it possible to obtain loans with over 100% of loan to value. The U.S. economic strategy after the „dot-com” crisis, contributed greatly to the formation of the real estate bubble. At that time, the Fed kept monetary conditions too loose, thus encouraging consumption in the U.S. market, as well as weakening the dollar by increasing the amount of the dollar and making products to be exported cheaper. In addition, the securitization of mortgage loans and the network of complex financial products further helped to shape the crisis. Complex financial products like CDO-s (collateralized debt obligation) and CDS-s (credit default swap) were broadly used among investment banks. A collateralized debt obligation (CDO) is a complex structured finance product that is backed by a pool of loans and other assets and sold to institutional investors. A credit default swap (CDS) is a financial derivative or contract that allows an investor to „swap” or offset his or her credit risk with that of another investor. Due to rising inflation, the Federal Reserve began to raise interest rates, which triggered the collapse of ARM loans. This process quickly spilled over to the financial market and then to the entire economy, and because of the central role of the United States to the entire world. The over-liberalized U.S. banking system, market and government failures directly contributed to the crisis, through the rise of subprime mortgages, securitization and deregulation.